A Note on John Kain's "Housing Segregation, Negro Employment, and Metropolitan Decentralization" - Masters, Stanley H. (Quarterly Journal of Economics, 1974)
Journal Article A Note on John Kain's "Housing Segregation, Negro Employment, and Metropolitan Decentralization" Get access Stanley H. Masters Stanley H. Masters University of Notre Dame Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 88, Issue 3, August 1974, Pages 505–512, https://doi.org/10.2307/1881951 Published: 01 August 1974